2014
DOI: 10.1111/jomf.12108
|View full text |Cite
|
Sign up to set email alerts
|

Husbands' Participation in Housework and Child Care in India

Abstract: The authors tested theories of housework among tea plantation workers in India, where women comprise the main part of the workforce and are breadwinners in their families. Analysis of 49 semistructured interviews and survey data from 3,181 female workers revealed that although women were mainly responsible for domestic labor, more than half of husbands usually or sometimes helped their wives with cooking, fuel wood collection, and child care. The analyses revealed a curvilinear relationship between husbands’ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…For example, in India (Weitzman, 2014), Bangladesh (Naved & Persson, 2005), Nicaragua, and the Dominican Republic (Kishor & Johnson, 2004) women's higher share of earnings are associated with higher physical and/or sexual violence from their spouses. Similar findings have been found for housework participation in India (Luke, Xu, & Thampi, 2003). In light of this evidence, I hypothesize that wives suddenly receiving a non‐negligible amount of money, via a welfare payment, could lead to “gender backlash” responses due to the transgression of traditional gender expectations.…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 86%
“…For example, in India (Weitzman, 2014), Bangladesh (Naved & Persson, 2005), Nicaragua, and the Dominican Republic (Kishor & Johnson, 2004) women's higher share of earnings are associated with higher physical and/or sexual violence from their spouses. Similar findings have been found for housework participation in India (Luke, Xu, & Thampi, 2003). In light of this evidence, I hypothesize that wives suddenly receiving a non‐negligible amount of money, via a welfare payment, could lead to “gender backlash” responses due to the transgression of traditional gender expectations.…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 86%
“…Spouses from lower socio-economic groups were accustomed to equal gender roles in the home and did not adhere rigidly to traditional customs. In contrast, Luke et al (2014) found in their study that husbands from lower socio-economic groups engaged to a lesser extent in domestic chores and childcare.…”
Section: Discussionmentioning
confidence: 38%
“…The difference in the time that men and women spend on unpaid work, such as household chores, cooking and childcare, has narrowed tremendously due to egalitarian gender views and an increase in women's marital power (Luke et al, 2014;Sullivan, 2011;Zimmerman, 2003). Husbands' greater involvement in housework could be attributed to wives having less time for these activities (Bianchi, Robinson, & Milkie, 2006).…”
Section: Household Chores and Childcarementioning
confidence: 99%
See 2 more Smart Citations